FORMING OF INTEGRAL PERCEPTION OF COLOR AND TONE FOR THE STUDENTS OF CREATIVE SPECIALTIES - Arkhipova, K.G.; Danilova, V.V. (PUBLISHINGS of Kostanay State Pedagogical University, 2018)
Forming of integral perception of color and tone by means of painting is considered as a psychological and pedagogical process in students’ education, during which, with the help of artistic and figurative reflection of objects of reality, a gradual increase in the artistic culture of students takes place.
Keywords: psychology of perception; fine art; painting; color; tone; artistic vision